Феномен социального капитала - Чепак, В.; Гугнин, Э. (Социология: теория, методы, маркетинг, 2001)
The authors analyse problems of rise, formation and transformation of social capital as a form of capital as such. The special feature of the work consists in the fact that it is the first attempt to analyse the social capital in the native sociology.